Review of some species in the genera Pselaphodes Westwood and Labomimus Sharp (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Li, Li-Zhen (Zootaxa, 2015)
Eight species of the genera Pselaphodes Westwood and Labomimus Sharp described from 1870 to 1925 are reviewed, six of them are redescribed, with their major diagnostic characters illustrated. Lectotypes are designated for the following names: Pselaphodes antennatus Bryant, 1915, Pselaphodes simplicicornis Champion, 1925, Pselaphodes spinosus Champion, 1925, and Pselaphodes villosus Westwood, 1870. Three new combinations and a new synonymy are proposed: Labomimus foveolatus (Raffray, 1882) comb. n. (transferred from Pselaphodes), Labomimus torticornis (Champion, 1925) comb. n. (transferred from Pselaphodes), and Pselaphodes championi (Jeannel, 1960) comb. n. (transferred from Labomimus), syn. n. (= Pselaphodes spinosus Champion, 1925).